RECOGNIZING THE PROFILE OF A FATHER IN ISLAMIC STUDIES AND ITS ROLE IN EDUCATION - Unik Hanifah Salsabila; Yazida Ichsan; Difa'ul Husna (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This paper describes how the Qur’an interprets and demonstrates the role of a father in the family as a Muslim Holy Book. Particularly the role of a child in a time of growth and mentality. A literature study on the content of the Qur’an in several relevant verses is conducted directly. In addition, a qualitative descriptive approach was used to conduct a phenomenological study on Muslim families in Indonesia. The author obtained an investigation of the verses of the Qur'an on the basis of this research which emphasizes the critical position. The nature of field observations also supports the findings of the literature. Researchers can draw conclusions about the role of fathers in family interaction on the cognitive competence of students